PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LKPD) MENGGUNAKAN LIVEWORKSHEETS PADA MATA PELAJARAN IPAS KELAS III SDN 12 KOTO BARU - M. Anggrayni; Sri Yunimar Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to develop teaching materials in the form of Electronic Student Worksheets (E-LKPD) using liveworksheets in the subject of Science for Class III SDN 12 Koto Baru, the type of research is Research & Development (R & D). Using the 4D development model includes 4 stages, namely the define stage, the design stage, the development stage, and the disseminate stage. The define stage, namely needs analysis, student characteristics analysis, curriculum analysis, LKPD analysis. Then the design stage, namely designing E-LKPD, teaching modules and instruments of validity, practicality and effectiveness. The development stage, namely the validation test of graphic experts, material/content experts, language experts, teaching module experts and question experts. The last stage is the dissemination stage, namely in addition to being carried out at SDN 12 Koto Baru, the researcher also disseminated it in Class III SDN 09 Koto Baru. The results of the validation of content or material, language and graphics obtained an average score of 92.8% in the very valid category. The validation test of the teaching module obtained an average score of 88.5% in the very valid category and the validation of questions obtained an average score of 86.6% in the very valid category. Then the practicality test assessed by teachers and students obtained an average score of 95.65% in the very practical category and the results of the effectiveness test in the form of multiple choice questions obtained an average score of 100% in the very effective category.